Considering the Legality and Legitimacy of Polygamy Without the First Wife's Permission: A Critique of Islamic Legal Epistemology by Mohammed Arkoun - Sulton Ariwibowo; Moh. Asror Yusuf; Moh. Safi'i Anam (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This article examines the legality and legitimacy of polygamy without the first wife's permission in contemporary Islamic family law through Mohammed Arkoun's critique of Islamic legal epistemology. Normatively, Indonesian positive law requires the first wife's consent and court approval as prerequisites for polygamy, yet in social practice polygamy is still frequently conducted outside these legal requirements. This tension reveals not merely a problem of legal compliance, but a deeper epistemological conflict between state law, ethical justice, and the sacralized authority of classical fiqh. Using a normative-theoretical method with an epistemological analysis of positive law, classical jurisprudence, and contemporary Islamic legal thought, this article argues that polygamy without the first wife's permission operates as a form of l'impensé (the unthinkable) within dominant Islamic legal reasoning. The article’s main theoretical contribution lies in reframing polygamy not as a doctrinal-legal exception, but as an epistemological problem rooted in the sacralization of fiqh and the exclusion of ethical and social experience from legal reasoning. By applying Arkoun’s critique of Islamic reason, this study proposes an epistemological reconstruction of Islamic family law that shifts the debate from textual permissibility toward ethical accountability and substantive justice.